Critical Discourse Analysis Ruth Wodak in The “ Bocah-Bocah Kosong” Youtube Video - Hetty Mery Marbun; Elly Manika Maya Mahadi; Gesilva Putri Samya Shaabiriina; Pramudya Ardhika Hernanto (Dinasti Publisher, 2025)
The entertainment industry is experiencing a notable evolution in humor, exemplified by the widely acclaimed content “Bocah-Bocah Kosong” on the YouTube WKWK Project by Genflix, which features women characterized by their oriental appearances and